Passive mapping for real-time monitoring of ultrasound therapy. - Coussios, C; Gyongy, M; Ritchie, R; Webb, I; Nandlall, S; Jackson, E; Arvanitis, C; Bazan-Peregrino, M; Arora, M (2010)
Arrays of detectors placed co-axially with a therapeutic transducer make it possible to receive the high-frequency emissions produced by tissue during therapeutic ultrasound excitation with high sensitivity and in real time, whether in the presence or absence of cavitation activity. The signals received by the array of receivers can be decomposed into broadband, harmonic, and ultraharmonic components and combined using recently developed passive mapping techniques to produce real-time maps of inertial cavitation, stable cavitation, boiling, and of regions of tissue where the high-frequency ultrasonic response changes significantly. In the context of high-intensity focused ultrasound ablation, passive mapping of inertial cavitation makes it possible to visualize the focus in real time, whilst mapping of boiling can identify regions of over-treatment. Further analysis of changes in the harmonic component of high-frequency emissions in the presence or absence of cavitation can also provide reliable detection of the change in viscoelastic tissue properties that corresponds to successful ablation. In the context of ultrasound-enhanced drug delivery, cavitation mapping can help identify the tissue regions where successful extravasation of therapeutic agents from blood vessels has occurred. It is concluded that passive mapping could provide a novel, effective, and low-cost method for real-time guidance and monitoring of ultrasound therapy.